Biosynthesis of Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) From Glucose by Escherichia coli Through Butyryl-CoA Formation Driven by Ccr-Emd Combination - Saito, Shu; Imai, Ryu; Miyahara, Yuki; Nakagawa, Mari; Orita, Izumi; Tsuge, Takeharu; Fukui, Toshiaki (Frontiers in Bioengineering and Biotechnology, 2022)
Poly[(R)-3-hydroxybutyrate-co-(R)-3-hydroxyhexanoate] [P(3HB-co-3HHx)] is a practical kind of bacterial polyhydroxyalkanoates (PHAs). A previous study has established an artificial pathway for the biosynthesis of P(3HB-co-3HHx) from structurally unrelated sugars in Ralstonia eutropha, in which crotonyl-CoA carboxylase/reductase (Ccr) and ethylmalonyl-CoA decarboxylase (Emd) are a key combination for generation of butyryl-CoA and the following chain elongation. This study focused on the installation of the artificial pathway into Escherichia coli. The recombinant strain of E. coli JM109 harboring 11 heterologous genes including Ccr and Emd produced P(3HB-co-3HHx) composed of 14 mol% 3HHx with 41 wt% of dry cellular weight from glucose. Further investigations revealed that the C6 monomer (R)-3HHx-CoA was not supplied by (R)-specific reduction of 3-oxohexanoyl-CoA but by (R)-specific hydration of 2-hexenoyl-CoA formed through reverse β-oxidation after the elongation from C4 to C6. While contribution of the reverse β-oxidation to the conversion of the C4 intermediates was very limited, crotonyl-CoA, a precursor of butyryl-CoA, was generated by dehydration of (R)-3HB-CoA. Several modifications previously reported for enhancement of bioproduction in E. coli were examined for the copolyester synthesis. Elimination of the global regulator Cra or PdhR as well as the block of acetate formation resulted in poor PHA synthesis. The strain lacking RNase G accumulated more PHA but with almost no 3HHx unit. Introduction of the phosphite oxidation system for regeneration of NADPH led to copolyester synthesis with the higher cellular content and higher 3HHx composition by two-stage cultivation with phosphite than those in the absence of phosphite.